1994
DOI: 10.1159/000284873
|View full text |Cite
|
Sign up to set email alerts
|

The Delusion of Inanimate Doubles

Abstract: A review of new cases of delusional misidentification reported between 1986 and 1992 suggests that the delusion of inanimate doubles is a variant of the Capgras phenomenon in approximately 10% of cases. It is argued that this variant makes current psychological theories of misidentification untenable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
0
9
0
5
Order By: Relevance
“…Feelings of derealization obviously form a prominent component of the clinical picture in many published cases of Capgras delusion and Cotard delusion. More precisely, Lewis (1987), Anderson (1988) and have suggested that the Capgras delusion involves damage to neuro-anatomical pathways responsible for appropriate emotional reactions to familiar visual stimuli. The delusion would then represent the patient's attempt to make sense of these puzzling changes.…”
Section: Discussionmentioning
confidence: 99%
“…Feelings of derealization obviously form a prominent component of the clinical picture in many published cases of Capgras delusion and Cotard delusion. More precisely, Lewis (1987), Anderson (1988) and have suggested that the Capgras delusion involves damage to neuro-anatomical pathways responsible for appropriate emotional reactions to familiar visual stimuli. The delusion would then represent the patient's attempt to make sense of these puzzling changes.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of CS has been reported among individuals of various ethnic backgrounds (11)(12)(13)(14)(15)(16)(17) and across a wide range of ages (14,(17)(18)(19)(20)(21)(22)(23)(24). The syndrome is exhibited in both sexes, although some authors have reported a higher prevalence among women (3,22,(25)(26)(27).…”
Section: Limitationsmentioning
confidence: 99%
“…1 The second group includes a belief that objects have been replaced by doubles and a belief that a significant person has been substituted by a near double. These two false beliefs correspond to the delusion of inanimate doubles 3 and Capgras delusion, 4 respectivel y, both of which are classifie d as DMSs. 2 Evans and Raistrick listed 12 phenomena that result from toluene intoxication.…”
Section: Discussionmentioning
confidence: 99%